Initial and Lower Magdalenian Large Mammal Faunas and Human Subsistence at El Mirón Cave (Cantabria, Spain) - Carvalho, Milena (2021)
In late Upper Paleolithic Cantabrian Spain, humans developed sophisticated territorial systems, used specialized lithic and osseous tools and weapons, and were skilled hunters of red deer and ibex while also depending increasingly on supplementary food resources, as means of adapting to climatic and environmental change after the Last Glacial Maximum. However, the specific effects of the environment on hunting decisions are not well understood for the early Magdalenian. Was subsistence specialization a byproduct of environmental change, does it reflect human population pressure and preferences, or are hunting strategies dictated by the geographic setting of El Miron? In this paper, we present the results of taphonomic and zooarchaeological analyses of Initial and Lower Magdalenian faunas from levels 119.2, 119, and 115 from El Miron, a large cave site in the Ason River valley of montane eastern Cantabria. We assess the human role in accumulation of these faunal assemblages and then explore whether there were differences in subsistence between the Initial and Lower Magdalenian. The results of this study complement analyses of other Magdalenian assemblages from El Miron and support the patterns of general continuity observed for the Cantabrian Magdalenian at several other regional sites.